The Structure/Pattern of Healing Miracle Narratives in the Gospels Performed Through “Touching” Jesus - Aryeh, Daniel Nii Aboagye (Biblical theology bulletin, 2024)
The structure/pattern of miracle narratives of Jesus in the gospels has been a critical area of attention for many form critics. The healing miracles of Jesus in the gospels have been studied and a general structure/pattern deduced. Although the structure/pattern propounded fit some healing miracles in the gospels, it does not adequately fit a group of healing miracle narratives in which victims (sick folks) touch Jesus. This study focuses on the Lukan version of the narrative of the woman with the hemorrhage (Luke 8:43-48) to propound a specific structure/pattern for healing miracle narratives in which victims touch Jesus to appropriate a healing miracle. Even though some aspects of the structure/pattern of healing miracles in which victims touch Jesus may share some similarities with the general structure/pattern of healing miracles asserted by form critics, no doubt, the structure/pattern of healing miracles in which victims touch Jesus is unique.